2020
DOI: 10.1055/a-1172-1352
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Conditions and COVID-19

Abstract: COVID-19 was declared a global pandemic by the WHO and has affected millions of patients around the world. COVID-19 disproportionately affects persons with endocrine conditions, thus putting them at an increased risk for severe disease. We discuss the mechanisms that place persons with endocrine conditions at an additional risk for severe COVID-19 and review the evidence. We also suggest prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 127 publications
(172 reference statements)
0
45
0
1
Order By: Relevance
“…This risk may be explained by a dysregulated immune response, a higher comorbidity burden, and alterations of ACE2 cellular expression [ 6 , 10-12 ]. The latter has been the subject of intense scrutiny, given the lack of evidence against the use of renin-angiotensin system blocking agents and their known benefits in diabetes and hypertension [ 12-14 ], as well as other cardiovascular conditions that have been shown to enhance ACE2 expression [ 15 ].…”
mentioning
confidence: 99%
“…This risk may be explained by a dysregulated immune response, a higher comorbidity burden, and alterations of ACE2 cellular expression [ 6 , 10-12 ]. The latter has been the subject of intense scrutiny, given the lack of evidence against the use of renin-angiotensin system blocking agents and their known benefits in diabetes and hypertension [ 12-14 ], as well as other cardiovascular conditions that have been shown to enhance ACE2 expression [ 15 ].…”
mentioning
confidence: 99%
“…The COVID-19 pandemic requires a joint effort from health care professionals of all areas of knowledge, including endocrinologists, to help fight the progress and consequences of the infection within their areas of expertise (4)(5)(6). Increasing evidence suggests that patients with prior endocrine diseases are at increased risk of developing severe COVID-19 (7)(8)(9), especially individuals with type 2 diabetes mellitus (10,11) or obesity (12), while data on thyroid involvement in SARS-CoV-2 infection are still scarce (13)(14)(15)(16). A few studies that have addressed this area of concern have found associations of COVID-19 infection with abnormalities of the pituitary-thyroid axis (17), subacute thyroiditis (18)(19)(20)(21), Hashimoto's thyroiditis (22), and thyrotoxicosis (23).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly significant as two in three adults in North America are overweight or have obesity [ 14 , 15 , 16 ], thus, a sustained period of weight gain during the pandemic could further aggravate metabolic syndrome [ 6 ]. This has implications for related health conditions like obesity [ 6 , 17 ] and its comorbid diseases, including diabetes [ 18 ], hypertension [ 18 ], and cardiovascular disease [ 19 ] that are significant risk factors for COVID-19 severity [ 20 ]. Indeed, half of patients hospitalized for COVID-19 have obesity [ 21 ], and patients with obesity are also more likely to require a ventilator [ 22 ].…”
Section: Introductionmentioning
confidence: 99%